At risk students in Malaysian secondary schools: Measuring attitudes towards schools and discovering multiple intelligences / Madihah Mohamad Shukri, Raja Zirwatul Aida Raja Ibrahim and Azlina Abu Bakar @ Mohd - Mohamad Shukri, Madihah; Raja Ibrahim, Raja Zirwatul Aida; Abu Bakar @ Mohd, Azlina (2004)
The term "student at risk" came into common use in educational field in the early 1980's, used to describe the students who are not successful, those who did not seem to fit in school. Although the issues of at risk students have been realized by many people especially among educators for decades yet, lately, the problems related to at risk students become more visible elsewhere. Moreover, identifying those at risk and how best to provide help appropriate their needs have come to the forefront. Thus, this study seeks to provide insight into helping students at risk by considering their perspectives of schooling and discovering their multiple intelligences. This was documented from a set of questionnaires. The targeted subjects consisted of 40 at risk students in three secondary schools. One of the most startling results is at risk students' responds indicating that they have fairly positive attitudes towards their schools. However, the peers and parental factors and not the learning variables may be the prominent causes that influence their positive attitudes and their reasons for attending school. Thus, the research suggests a call for transformation of schooling system from typical classroom to a new one, which caters diversity of interest, talents, skills and intelligences. There are also the needs for comprehensive academic and non-academic programs that highlight the importance of having a collaborative partnership between home, school and community.